Optimalisasi Manajemen Layanan BK melalui Analisis Kebutuhan dan Kolaborasi Staf Sekolah - Christiana, Elisabeth; Rahmwati, Maria Yustiana; Prasetyo, Intan Anggraheni Zahrin; Hakiki, Intan Ainul; Purnama, Ivan Fadillah Putra (TSAQOFAH, 2025)
This research aims to optimize the management of guidance and counseling (BK) services in schools through needs analysis and collaboration of school staff. By identifying specific student needs and involving various parties within the school environment, guidance and counseling services can be designed and implemented more effectively. Collaboration between counselors, teachers and other school staff is expected to improve the quality of guidance and counseling services, so that they can provide more comprehensive support for students' academic and psychological development.